A Longitudinal Study of Freshmen ELT Students’ Proficiency: A Case Study - Korun, Gülsün (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
With English being the most popularly taught and learnt foreign language nowadays, institutions such as the 5 private/state-trust universities in North Cyprus have adopted English medium education so as to fulfil both the societal and educational requisites. The English Language Teaching departments obviously take the lead and conduct their profession related courses via the English medium thus ensuring the continuous linguistic development of the students. Unfortunately, these courses have been transformed into language learning sessions for the students whose language competency at the end of their four-year undergraduate study continues to be debatable. This study encompasses two main purposes; firstly, to determine if the English language development of the EMU English Language Teaching Freshmen students is acceptably adequate, and secondly, to compare the English competency of 5 groups of students with regards to predefined social and economic parameters. The first part of the research is a longitudinal study involving continuous testing and assessment of students‟ language abilities both in English and in Turkish. The latter part assesses the students‟ language competency at a specific time instant. Data are collected via pre-test/post-test design by employing a recognised test battery, 2 writing tasks and a questionnaire. The data are analysed quantitatively with Paired-Sample T-test, Independent Samples T-test, Kruskal Wallis Test, Mann-Whitney U test, One-way Anova, Pearson Correlation and Linear Regression. The study concludes that students‟ English language skills are positively reinforced over a period of two semesters, with the departmental vocational and language courses progressively supporting the improvement of their language competence. The results also argue that there is no significant difference in students‟ language competency with respect to genders, and yet there is a significant correlation between students‟ language competency and their socio-economic-cultural background. Additionally, the study claims that there is a significant difference between students‟ L1, Turkish, and L2, English, competencies and there is hardly any correlation between their L1 and L2 writing skills. Finally, when all five universities are compared with respect to their students‟ language test results, a significant difference between and among the universities is observed. Keywords: Content Language Integrated Learning, Content Based Instruction, English medium education, immersion education, language interdependence, lingua franca

ÖZ: Günümüzde yabancı dil olarak İngilizce dünyanın her yerinde yoğun bir şekilde kullanılırken, bu çalışmanın yapıldığı zamanda Kuzey Kıbrıs‟taki 3 özel ve 2 vakıf üniversitesinin (halen 12 özel, 2 vakıf) de İngilizce dilinde eğitim verme yönündeki kararları yadsınamaz. Elbette ki bu üniversitelerde İngilizce dil öğretimi bölümleri bu kararı uygulamada öncelik taşımaktadırlar. Bunun altında yatan temel düşünce de öğrencilerinin eğitim süresince İngilizce dil becerilerini mesleki ve dil geliştirme dersleri sayesinde ilerletecekleri umududur. Ancak 4 yıllık eğitim süresinin sonunda, beklenen bu gelişme tartışılacak boyuttadır. Bu çalışma bir ilk örnek çalışma olup, çalışmanın ilk bölümünde bir vaka incelemesi yer almaktadır. Çalışmanın iki temel amacından birincisi DAÜ‟de İngilizce öğretmenliği eğitimi alan birinci ve ikinci sınıf öğrencilerin İngilizce dil yetilerinin dört yıllık süreçte yeterli ve hedeflenen seviyeye ulaşıp ulaşmadığını tespit etmek, ikincisi de 5 üniversitenin tümünde birinci sınıf öğrencilerinin daha önceden belirlenen sosyo-ekonomik ve kültürel ölçütler çerçevesinde dil yetilerini kıyaslayarak ölçmektir. Çalışmanın birinci aşaması uzun süreli olup, veriler tekrarlanan test yöntemi ve anketle toplanmıştır. Tüm üniversitelerden kıyaslama amacı ile toplanan veriler ise tek seferde ve aynı zaman diliminde elde edilmiştir. Sonuçlar nicelik değerlendirme ile incelenmiş olup kullanılan testler de Eşleştirilmiş Örneklemeler T Testi, Bağımsız İki Örneklem T Testi, Kruskal Wallis Sıralamalı Tek Yönlü Varyans Analizi Testi, Mann-Whitney U Testi, Tek-yönlü Anova, Pearson Korelasyon ve Linear Regresyon‟dur. Çalışmanın sonuçlarına göre DAÜ İngilizce öğretmenliği bölümündeki öğrencilerin dil yetileri iki dönemin sonunda bir ilerleme kaydetmekte olup, mesleki ve dil geliştirme derslerinin bu gelişmeye katkısı olduğu gözlemlenmiştir. Çalışma aynı zamanda cinsiyetin dil becerisi ile bir bağlantısı olmamakla birlikte, sosyoekonomik ve kültürel seviye ile ilişkisi olduğunu göstermiştir. Ayrıca, araştırmaya gore deneklerin İngilizce ve Türkçe yazma becerileri benzerlik göstermedikleri gibi, aralarında korelasyonun da neredeyse hiç bulunmadığı tespit edilmiştir. Son olarak, çalışmaya katılan 5 üniversitenin öğrencilerinin İngilizce yetileri arasında belirgin bir farka da rastlanmıştır. Anahtar Kelimeler: İçerik ve Dil Entegreli Öğrenme (CLIL), İçerik Tabanlı Dil Eğitimi (CBI), İngiliz Dilinde Eğitimi(EMI), Kaynaştırma Eğitimi, dil bağımlılığı, geçer dil
Doctor of Philosophy in English Language Teaching (ELT). Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2016. Supervisor: Prof. Dr. Necdet Osam.
Keywords: English Language Teaching (ELT); English Language-Study and Teaching; English language--Study and teaching-ELT Students-Proficiency-Eastern Mediterranean University-Cyprus, North; Content Language Integrated Learning; Content Based Instruction; English medium education; immersion education; language interdependence; lingua franca